The antecedents of financial health in Malaysia with the mediating effect of financial vulnerability - Sabri, Mohamad Fazli; Wijekoon, Rusitha; Burhan, Nik Ahmad Sufian; Abd Rahim, Husniyah; Othman, Mohd. Amim; Magli, Amirah Shazana (Malaysian Consumer and Family Economics Association MACFEA, 2022)
Though financial experts have examined financial health antecedents to understand the concept properly, inconsistencies are still existing in this critical concept due to the individual differences among the people. Hence, the major objective of the current study is to examine the drivers of financial health for the Malaysian context to encourage their financial plans for achieving their future life goals. A questionnaire survey was conducted among Malaysian households who were selected using the multi-stage random sampling method. Based on the PLS-SEM analyses, all the direct and indirect relationships tested were revealed significant. Psychological construct; self-efficacy, financial factors; money attitudes, financial behavior, and financial vulnerability were identified as significant drivers of financial health, and except, financial vulnerability, all the other variables were found to positively influence the financial health of Malaysians. Altogether, they clarified 56.3% of the variance in financial health. Further, self-efficacy, money attitudes, financial behavior affected negatively financial vulnerability and explained 48.8% of the variance effectively. Moreover, self-efficacy, money attitudes, and financial behavior were assumed to have significant effects on financial health through financial vulnerability, and all the mediating effects were found significant. The current study widens the understanding of both the determinants of financial vulnerability, and financial health which guide financial experts, academicians, and policymakers to design policy guidelines to enhance the financial health of the general public. Furthermore, the findings of this study will assist the government and non-governmental organizations (NGOs) in developing a holistic approach aimed at improving the living standards and financial health of Malaysia's lower-income households.